STABILITY FOR TUBER YIELD AND ITS COMPONENTS IN POTATO - Luthra, S. K; Gopal, J.; Singh, B. P.; Pandey, S. K. (Potato Journal, 2013)
Thirty four potato genotypes were evaluated for tuber yield and its components at two harvesting dates in early and main crops during two consecutive crop seasons for identifying stable genotypes. In early crop, Kufri Surya and in main crop Kufri Arun, Kufri Sutlej and MS/97-621 were found responsive for total tuber yield. The genotypes CP3359, MS/93-1344, MS/94-899 and MS/98-6955 were found ideally stable for tuber yield over the environments. CP3359 was an ideally stable genotype for tuber yield components across the environments.